Encephalopathy Associated With Neurochondrin Autoantibodies. (October 2019) - Schumacher, Myriam; Rommel, Frank Risto; Arneth, Borros; Renz, Harald; Stöcker, Winfried; Windhorst, Anita; Hahn, Andreas; Neubauer, Bernd Axel
We determined the prevalence of autoantibodies against an extended number of established and novel neural antigens in children and adolescents with suspected autoimmune encephalitis, epilepsy, single seizures, or marked epileptiform activity in electroencephalography (EEG). Prospectively, 103 patients were recruited aged between 0 and 18 years and 104 controls. A panel of 35 autoantibodies against neural cell-surface and intracellular antigens was screened. Sixteen of 103 patients (15.5%) showed a positive result for 1 or more autoantibodies, compared to 6 of 104 controls (5.8%, P = .02). Neurochondrin was identified as a possible new target of autoantibodies in 3 patients within this cohort, but none in controls. The patients showed severe behavioral disturbances, memory and cognitive impairment, episodes of reduced responsiveness, but no seizures, and normal MRI. Clinical findings, course, and treatment response of these 3 patients are presented.